Accounting Disclosure for non-current intangible assets according to international accounting standard (IAS16, 36): A Comparative Study of the State Company for Travelers and delegates Transportations (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The Accounting Disclosure for non-current intangible assets is necessary to rely on accounting information by decision makers in the economic unity, two international accounting standards issued (IAS16,36), which aims to provide the foundations of the recognition, measurement and disclosure of appropriate assets Non-current tangible. (IAS16) allowed to use re-evaluation approach to measure assets entrance due to the inadequacy of the accounting information resulting from the application of the historical cost of the entrance under increasing technical developments and continuing that leave clear their effects on non-current intangible assets, As well as the requirements of what came (IAS36) the importance of accounting for the impairment of assets that require immediate recognition of losses resulting from the decline value of those assets as an important financial data from accounting of what they contain information useful to the appropriateness of the decisions of its users quality indicators. The research aims to demonstrate the impact of the application of international accounting standard (IAS16,36) on the financial statements and the importance of accounting disclosure for assets that impairment in value as well as the development of accounting applications contained in the uniform accounting system in line with changes in the economic environment, developments guided through the requirements of the two standards above and adapted according to the Iraqi environment. The research has come to a set of conclusions, including: Iraqi environmental lack of accounting to accounting rule governing the respect of intangible assets and its depreciations as well as a unified accounting system 's reliance on the historical cost basis for the registration of economic events and the lack of recognition of the value of such decline assets. It recommended the issuance of a private accounting rule assets Non-current tangible and disclose the drop -winning value her and forcing economic units to apply international accounting standard requirements (IAS16,36), given their importance in strengthening the appropriateness of accounting information property.